An Exploratory Study of the Perceived Benefits of Electronic Bulletin Board Use and Their Impact on Other Communication Activities Michael L. James and Others. - James, Michael L. (Distributed by ERIC Clearinghouse, 1993)
Characteristics of users of electronic bulletin boards, the perceived impact that bulletin boards have on users, and how their use affects the use of other communications media were studied using a random sample of users of CompuServe and Prodigy, two major bulletin board services. Respondents (95 for CompuServe and 78 for Prodigy) were interviewed asynchronously on-line through electronic mail. Results of the on-line survey support adoption hypotheses that suggest that bulletin board users are more highly educated and more wealthy, and work in more prestigious occupations than does the average American. A similar lower-age hypothesis was rejected. Open-ended responses to the question "Why use boards?" were content analyzed. Hypotheses suggesting a reduction of consumption of the media television, books, telephone use, and personal letter writing were supported. Rejected were lower magazine reading, face-to-face conversations, and other on-line communication. Findings also show significant differences in the CompuServe and Prodigy systems along several of the variables mentioned above, in addition to amount of use, message rate, and family usage patterns. Seven tables present study findings. (Contains 54 references.) (SLD)